BRAF/MEK inhibitors use for pediatric gliomas; real world experience from a resource-limited country - Abu Laban, Dima; Alsharif, Abeer; Al-Hussaini, Maysa; Obeidat, Mouness; Maraqa, Bayan; Alzoubi, Qasem; Musharbash, Awni; Jaddoua, Saad; Ramlawi, Raed; Khaleifeh, Kawther; Ibrahimi, Ahmad Kh.; Sarhan, Nasim; et al. (Frontiers in Oncology, 2024)
IntroductionMost pediatric low-grade-gliomas (LGG) and some high-grade-gliomas (HGG) have alterations in the RAS/MAPK pathway. Promising high tumor response rates were achieved using BRAF/MEK inhibitors, however data on their use in low-middle-income-countries (LMICs) are limited.MethodsWe retrospectively reviewed our Jordanian experience of using compassionate BRAF/MEK inhibitors in treating children with gliomas. We reviewed patients’ clinical characteristics, tumor response, and side effects.ResultsTwenty patients (13 males, 7 females) were identified. Median age at diagnosis was 8.3 years (0.3-18.9years). There were fifteen LGGs, three HGGs and two grade-2 pleomorphic xanthoastrocytoma (PXA-2). Fifteen tumors were supratentorial, three posterior fossa/brainstem, one diffuse-glioneuronal tumor (DLGNT) and one spinal. Five tumors were metastatic. Except for one patient with neurofibromatosis, ten patients underwent partial resection and nine had biopsy. All patients, except three, received BRAF/MEK inhibitors after initial standard chemo/radiotherapy. Seven LGGs had BRAF-mutation, six had BRAF-fusion, and two were empirically treated (one neurofibromatosis and one DLGNT). Fourteen LGGs were treated with 1-4 chemotherapy regimens before BRAF/MEK inhibitors’ use; all had partial/stable response on targeted therapy at a median of 1.9 years (0.5-5.4years). Two patients with BRAFv600E-mutated/CDKN2A deleted PXA-2, had progression following resection, and experienced stable/partial response at 9 months of dabrafenib use. Two patients with HGGs had BRAFv600E-mutation, and one had an FGFR-mutation. All three patients with HGG had temporary stable/partial response, two with significant clinical improvement. At a median of 2.7 years (1.3-3.2years), all patients experienced tumor progression, and two died. Eight patients (40%) developed acneiform rash, three (15%) paronychia, and one had significant panniculitis and fatigue. Six patients (30%) needed dose-reduction. Nine patients had temporary drug interruptions [due to side effects (5) and drug shortage (4)]. Two patients who stopped trametinib due to side effects (significant acneiform rash/paronychia and intracranial bleeding) did not experience progression.ConclusionsOur experience with BRAF/MEK inhibitors’ use was positive achieving response in all LGGs and provided sustained response with good quality of life for patients with HGG. Cost effectiveness analyses and patients’ satisfaction comparisons with chemotherapy are needed to evaluate the routine use of these drugs in LMICs.